Killing premiers to build a canal: McLeod Stewart and the Montreal, Ottawa and Georgian Bay Canal - White, Daryl (Ontario History)

(untitled) (The Ontario Historical Society, 2007)
For more than a century, Canadian promoters encouraged the construction of the Montreal, Ottawa and Georgian Bay Canal. No individual brought more passion to the cause than McLeod Stewart. A well-connected man, he was a former Mayor of Ottawa and involved in a number of ventures in the city. He devoted more than two decades of his life to raising private and public support for the canal he felt would capture the trade of the North American interior for Canada. Stewart may have failed to realize his dream, but his optimistic imperialism reminds us of the spirit which infused Canada in the Laurier years.